Polymer-Peat Column as an Improvement of Soil Settlement - Muhammad, Nur Shaffa Syafwah; Mohd Hairul Azekey, Nur Adriana Nabila; Muhammad Aiman Azhar; Siti Nooraiin Mohd Razali (Multidisciplinary Applied Research and Innovation, 2025)
Peat is a weak soil with high organic content, high moisture content, high compressibility, and low shear strength. Due to its nature that requires a stabilization process, an experimental model study of the Polymer-Peat Column (PPC) is conducted. The study’s objectives are to identify the performances of the PPC in a physical model study and to study the soil structure interaction between load, settlement and time. A physical model in this study is a method used to identify the performances of the PPC in a peat soil. The original peat soil was placed in a box of 30 cm x 30 cm x 30 cm as a soil bed allowing it to rest for 24 hours promotes homogeneity. The study highlighted the variations in settlement while employing PPC versus without PPC. Peat is a primary material and Vinyl Acetate-Acryl Copolymer (VAAC) is used as a stabilizer agent to improve soil settlement. The result of this study shows when maximum load in this study is applied to peat soil without PPC is 7.023 mm and 12 cm from the center shows 0.028 mm. While the result for settlement with PPC is 6.515 mm after applying load and 12 cm from the center is 0.024 mm. In contrast, peat soil without PPC experiences greater settlement due to its high compressibility and low shear strength, leading to increased deformation under load. Thus, VAAC is an effective chemical stabilizer that can reduce peat soil settlement. These findings support the adoption of VAAC as an effective solution for addressing settlement issues in peat soils, offering a viable approach for infrastructure development in areas characterized by these challenging soil conditions.